Diacerein Inhibits Myopia Progression through Lowering Inflammation in Retinal Pigment Epithelial Cell. (5th July 2021) - Tien, Peng-Tai; Lin, Chia-Hung; Chen, Chih-Sheng; Chang, Ching-Yao; Ku, Hsiangyu; Gan, Dekang; Tsai, Yi-Yu; Chen, Jamie Jiin-Yi; Lin, Hui-Ju; Wan, Lei
Abstract : Myopia is a highly prevalent refractive disorder. We investigated the effect of diacerein on monocular form deprivation (MFD) in hamsters as a possible therapeutic intervention. Diacerein is an anthraquinone derivative drug whose active metabolite is rhein. Diacerein or atropine was applied to the MFD hamsters, and their refractive error and axial length were measured after 21 days. The refractive error (control: − 0.91 ± 0.023, atropine: − 0.3 ± 0.08, and diacerein: − 0.27 ± 0.07   D ) and axial length (control: 0.401 ± 0.017, atropine: 0.326 ± 0.017, and diacerein: 0.334 ± 0.016   mm ) showed statistically significant differences between control, atropine-treated, and diacerein-treated MFD eyes. Furthermore, we determined the level of transforming growth factor-beta- (TGF-) β 1, matrix metalloproteinase- (MMP-) 2, type I collagen, interleukin- (IL-) 6, IL-8, and monocyte chemoattractant protein- (MCP-) 1 in the retina. Atropine and diacerein suppressed levels of the myopia-related TGF- β 1 and MMP-2 while increasing type I collagen expression. They also inhibited the interleukin IL-6, IL-8, and MCP-1 levels. Diacerein reduced the IL-6, IL-8, and MCP-1 expression in ARPE-19 cells. Furthermore, diacerein inhibited inflammation by attenuating the phosphorylation of protein kinase B (AKT) and nuclear factor kappa-light-chain-enhancer of activated B (NF- κ B) pathway. This suggests that diacerein has a therapeutic effect on myopia and is a potential treatment option.